Порівняння методів розрахунку плитних фундаментів з урахуванням результатів інженерно-геологічних вишукувань та геодезичних спостережень за процесом просідання - Пашинський, В. А.; Тихий, А. А.; Пашинський, М. В.; Карпушин, С. О.; Яцун, В. В.; Pashynskyi, V.; Tykhyi, A.; Pashynskyi, M.; Karpushyn, S.; Yatsun, V. (ЦНТУ, 2022)
На прикладі фундаменту під силос зерносховища у вигляді круглої залізобетонної плити діаметром 20,4 м виконане порівняння трьох методів розрахунку осідання суцільних плитних фундаментів. Розрахунки за моделлю плити на пружній основі та за моделлю об'ємних скінченних елементів дали середні значення осідання 2,15 см та 2,4 см, близькі до фактичної величини 1,75 см, отриманої за результатами натурних геодезичних спостережень, що велися з початку будівництва об'єкту. Регламентований чинними нормами проектування розрахунок за методом пошарового підсумовування дав різко завищений результат 13,7 см. Increasing the height of buildings and structures in combination with the development of areas with unfavorable geotechnical conditions cause the use of foundations in the form of solid reinforced concrete slabs. In complex geotechnical conditions and under high loads, the soils can work beyond linear deformation. This necessitates the calculation of the system "building-foundation-soil" based on the assumptions of nonlinear soil mechanics. The issue of designing foundations for cylindrical structures of the agro-industrial complex, in particular granaries, is especially relevant. The task of this study is a comparative analysis of different methods for calculating the subsidence of slab foundations to select a rational model of deformation of the soil. The comparison of calculation methods is carried out on the example of the foundation under the granary with a volume of 8841 m3. The foundation is made in the form of a round reinforced concrete slab with a diameter of 20.4 m. The characteristics of the soil are established by the results of geotechnical surveys. The calculation according to the Winkler model (elastic base plate with one coefficient of subgrade reaction) was performed in the "Cross" module of the SCAD Office software package. With a total load on the foundation of 2741 tf, its average subsidence is 2.15 cm. The calculation according to the model of three-dimensional finite elements of cubic shape was performed in the environment of the SCAD Office software package. The average subsidence of the foundation is 2.4 cm. The calculation by the method of layer-by-layer summation according to the instructions of DBN B.2.1-10: 2018 gave the subsidence of the foundation slab equal to 13.7 cm. The actual average subsidence of the foundation during the observation period in different areas of the foundation was 1.1… 2.4 cm and averaged 1.75 cm. The comparison of the analyzed methods for determining the subsidence of the foundation indicates the closeness of the results of calculations on the model of the slab on an elastic basis and the model of three-dimensional finite elements to the actual value of subsidence and the greatly higher result of the calculation by layer summation. The use of the latter method leads to excessive reliability in the design of foundations.
Comparison of Methods for Calculating Slab Foundations, Taking Into Account the Results of Geotechnical Surveys and Geodetic Observations of the Subsidence Process
Keywords: плитні фундаменти; осідання; методи розрахунку; slab foundations; subsidence; calculation methods